Pharmacist intervention to enhance postoperative fluid prescribing practice in an Iraqi hospital through implementation of NICE guideline - Abbood SK; Assad HC; Al-Jumaili AA (Centro de Investigaciones y Publicaciones Farmaceuticas, 2019)
Objective: The objectives of this study were to evaluate the current practice of postoperative fluid prescribing and assess the effectiveness of pharmacist-led intervention in the implementation of the National Institute of Health and Care Excellence (NICE) fluid therapy guideline in an Iraqi hospital. Methods: The prospective interventional study was conducted at AL-Hilla Teaching Hospital, Babylon, Iraq between November 2017 and July 2018. The study included two phases: The pre-intervention phase with 84 patients and the post-intervention phase with 112 patients. A pharmacist provided training and educational sessions for the hospital physicians and pharmacists about the NICE guideline of fluid therapy. The researcher calculated the amount of given post-operative fluids and compared to the NICE guideline and also measured the patients' body weight, serum Na, K and creatinine pre-and post-operatively. Results: The pre-intervention phase showed no correlation between the amounts of prescribed fluids and body weight which caused increases in patients' body weight. In pre-intervention phase, 6% of patients experienced hyponatremia, 19% had hypernatremia and 7.1% had hypokalemia. In the post-intervention phase, abnormal level of electrolytes and patient weight gain decreased significantly. Additionally, the intervention led to a strong correlation between body weight and amount of prescribed fluids in addition to lowering the incidence of electrolyte disturbances. Conclusions: A high proportion of patients in the pre-intervention phase experienced fluid overload, weight gain and electrolyte disturbances when fluid therapy was not prescribed in accordance with the NICE guidelines. The pharmacist-led intervention increased the surgeon awareness of the proper use of the NICE guideline which decreased the incidence of fluid-related complications and the inconsistency of fluid prescribing. Pharmacists can play a critical role to enhance post-operative fluid prescribing and minimize fluid-induced complications.